Teachers’ Perceptions On Teaching Cohesion To Efl Graduate Students At Mohamed Lamine Debaghine Setif 2 University - Ais, Hamza (جامعة الوادي - University of Eloued, 2021)
The current probe explores teachers’ experiences in teaching cohesion for essay writing. It describes their assistance for learners to produce cohesive writing compositions. For data collection, semi-structured interviews with 05 teachers of written expression and academic writing were conducted. Thematic analysis of interviewees’ responses revealed that students’ lack of exposure to English and English collocations are two major reasons behind failure in writing cohesive essays. Time constraints limited learners to less practice in writing classes; therefore, learners should be encouraged to extensive reading. Teaching hours for written expression should be expanded to create opportunities for more practice.
Article
Keywords: English collocations; essay writing; extensive reading; teachers’ experiences; teaching cohesion